The Impact of Understanding of Translation Techniques on the Quality Translations: Case Study: English Language and Literature Students of Study Program in Translation-Universitas Terbuka (UT) (Universitas Terbuka, 2023)
This article aims to describe the impact of students' understanding of translation techniques to produce quality translations. The method used is a semi-experimental method by giving a pretest and posttest in the form of two English source texts of technology that are considered quite familiar to students. First, students were given a pretest to determine students' initial abilities before being given material about translation techniques. Then, before doing the posttest, students were given an understanding of translation techniques. After that, students were given a posttest to see their understanding of the use of translation techniques to produce quality translations. This research is a case study that applies a qualitative approach using content analysis techniques. An important result of this study is the understanding of translation techniques by using the appropriate translation techniques has an impact on quality translation based on three indicators of quality translation: accurate, natural, and acceptable in the culture of the target readers.